Kucing Sebagai Ide dalam Penciptaan Karya Seni Lukis - Putri R., Lintang Diani; Yudha, I Made Bendi; Gulendra, I Wayan (PROGRAM STUDI SENI MURNI ISI DENPASAR, 2023)
Everyone has their own way of expressing their relationship with pets like cats. The process of creating a work of art is closely related to the experiences experienced such as emotional closeness with cats and experiences full of feelings and thoughts in everyday life that are excited. This uniqueness gives rise to a sense of expressing it through creativity and imagination into the form of paintings using various techniques, media, taking into account the elements and principles of art. There is a method from Alma M. Hawkins as a reference at the stage of making this painting, including exploration, improvisation, and forming. The artwork created displays visuals that lead to naive forms with freedom in processing shapes and expressing lines that do not depend on the original object.